Effects of bio-extract from pineapple peel on the germination and growth of pea (Lathyrus oleraceus Lam.) - Kaeonuan, Santichai; Nunto, Wipawan (Journal of Science and Technology CRRU, 2024)
This research aims to study the effects of pineapple peel bio-extracts on the germination and growth of green peas. The bio-extract was diluted at ratios of 1:100, 1:200, 1:300, 1:400, and 1:500 (v/v) with water. Germination percentage was studied by soaking healthy pea seeds in bio-extract solutions of various dilutions compared to distilled water for 8 hours, then sowing them on germination dishes using the Top of paper method and watering with distilled water and bio-extract solutions at the previously mentioned dilution ratios for 48 hours. The appropriate concentration of bio-extract that resulted in the highest germination rate was found to be 1:200, with a percentage of 76.67 ± 5.03, whereas the control group had a germination rate of 58.33 ± 5.03. For the growth study of pea seedlings, the seeds were soaked in bio-extract for 2 hours, then planted on germination trays and watered with bio-extract solutions at different dilution levels compared to distilled water twice a day. The height and stem diameter of the seedlings were measured on days 2, 4, 6, 8, and 10, and the fresh weight was measured on day 10 of the experiment. It was found that the bio-extract solution at a dilution level of 1:200 resulted in pea seedlings with a height, stem diameter, and fresh weight on day 10 of 10.51 ± 0.87 centimeters, 2.20 ± 0.17 millimeters, and 1.97 ± 0.06 grams, respectively. This was compared to the control group with measurements of 7.39 ± 1.65 centimeters, 2.16 ± 0.40 millimeters, and 1.67 ± 0.40 grams, respectively.